Selection Of Project Managers In Construction Firms Using Analytic Hierarchy Process (AHP) And Fuzzy Topsis: A Case Study - Torfi, Fatemeh; Rashidi, Abbas (Penerbit Universiti Sains Malaysia, 2011)
Selecting a project manager is a major decision for every construction company. Traditionally, a project manager is selected by interviewing applicants and evaluating their capabilities by considering the special requirements of the project. The interviews are usually conducted by senior managers, and the selection of the best candidate depends on their opinions. Thus, the results may not be completely reliable. Moreover, conducting interviews for a large group of candidates is time-consuming. Thus, there is a need for computational models that can be used to select the most suitable applicant, given the project specifications and the applicants’ details. In this paper, a case study is performed in which a Fuzzy Multiple Criteria Decision Making (FMCDM) model is used to select the best candidate for the post of project manager in a large construction firm. First, with the opinions of the senior managers, all the criteria and sub-criteria required for the selection are gathered, and the criteria priorities are qualitatively specified. Then, the applicants are ranked using the Analytic Hierarchy Process (AHP), approximate weights of the criteria, and fuzzy technique for order performance by similarity to ideal solution (TOPSIS). The results of the case study are shown to be satisfactory.